Drug permeation and barrier damage in Leishmania-infected mouse skin. (21st February 2016) - Van Bocxlaer, Katrien; Yardley, Vanessa; Murdan, Sudaxshina; Croft, Simon L.
Abstract: Objectives: Pathological disorder can disrupt the barrier integrity of the skin, thereby altering the drug delivery from topical formulations to the target site. Cutaneous leishmaniasis (CL) is an infection of the dermal layers of the skin and manifests as a variety of skin lesions from defined nodular forms to plaques and chronic ulcers. The aim of this work was to characterize the physiology and barrier integrity of the Leishmania -infected BALB/c mouse skin and how they impacted delivery of drugs into the skin. Methods: A histological evaluation of the structural differences between uninfected and infected skin was performed using haematoxylin/eosin, elastic Van Gieson and Iba-1 stains. As a CL nodule developed and progressed, the skin pH, hydration and trans-epidermal water loss (TEWL) were recorded. Finally, Franz diffusion cells were used to evaluate the influence of the infection on drug delivery through the skin. Results: We found: (i) structural changes in both the epidermal and dermal layers due to the ingress of inflammatory cells, as shown by immunohistochemistry; (ii) a significant increase in TEWL; and (iii) significantly higher permeation of the model permeants caffeine and ibuprofen and the antileishmanial drugs buparvaquone and paromomycin, for Leishmania -infected skin compared with uninfected skin. The infection had no measurable influence on skin pH and hydration. Conclusions: We report profound changes in the skin barrier physiology, function and permeability to drugs of Leishmania -infected skin.